Analysis of multi server Markovian queue with functioning vacation and intolerance of customer - Shanmugasundaram, S; Murugesan, R (International Journal of Engineering and Technology, 2018)
In this article, we analyze the operating behavior of two server Markovian queueing model with functioning vacation and infinite population. If the server is halt his service suddenly in a normal busy period and repair work is done immediately and service starts. The server failure and repair rates are follow exponential distribution, when the system become vacation the server takes functioning during this period the customer wait in the queue and server serves the customer with the lower service rate. The steady state behavior is also obtained, the various performance measures are also determined. The numerical example is given to test the feasibility of the model.Â Â Â Â